Between Europeanisation and Corporatisation: Poland's Nation Branding and Soft Power for Public Consumption. Issue 4 (November 2021) - Surowiec, Paweł
Focusing on the "state" rather than the "nation, " this article explores the interplay between nation branding and Poland's soft power statecraft. Contextualised by Poland's European orientation in foreign affairs, this Bourdieusian study focuses on the field of diplomacy and statecraft, particularly its communicative practices for the articulation of soft power. Aided by policy documents and campaign artefacts, this analysis of interviews (n=45) with state actors and newcomers to the field, nation branders, traces their actions, and unfolds the effects of their practices on soft power statecraft. The central argument emerging from the analysis of findings rests on the cultural conditions and ideological effects of nation branding on the field. On the one hand, I find, these effects advance the process of "corporatisation" of Poland's soft power statecraft. On the other hand, the embeddedness of nation branding in Poland marks a cultural shift in soft power statecraft towards technocratic and transactional promotional culture.